Konsep Frugal Living dalam Surah Al-An’am : 141 Perspektif Moh. E. Hasim dalam Tafsir Ayat Suci Lenyepaneun - Ahmad Latif Tsauri; Abd Aziz; Badru Tamam (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This study stems from the phenomenon of the rise of a consumerist lifestyle in modern society, which has led to various economic, social, and environmental issues. The study aims to examine the concept of frugal living in this verse through the perspective of Sundanese exegesis, specifically in the exegesis *Ayat Suci Lenyepaneun* by Moh. E. Hasim. This study employs a qualitative approach using library research. Primary data was obtained from the interpretation of Al-An'am 141 in the “Ayat Suci Lenyepaneun” exegesis, while secondary data was sourced from various literature related to exegetical studies, the concept of frugal living, and Sundanese cultural values. Data analysis was conducted using an analytical exegetical approach combined with a descriptive-analytical method to uncover the meaning of the verse and its relevance to the concept of frugal living in Islam. The results of the study indicate that Moh. E. Hasim’s exegesis emphasizes the importance of a simple attitude, the wise management of wealth, and the prohibition of wasteful behavior as part of Islamic consumption ethics. These concepts are not only oriented toward economic savings but also possess spiritual, social, and ecological dimensions. The novelty of this study lies in its effort to link the concept of frugal living with local Sundanese exegesis, thereby demonstrating how the values of the Qur’an can be understood contextually within the framework of Nusantara culture.